Best Answer

[(-4) + (-3)]*[(-2 - (-1)] = (-4 -3)*(-2 + 1) = -7*-1 = +7

[(-4) + (-3)]*[(-2 - (-1)] = (-4 -3)*(-2 + 1) = -7*-1 = +7

[(-4) + (-3)]*[(-2 - (-1)] = (-4 -3)*(-2 + 1) = -7*-1 = +7

[(-4) + (-3)]*[(-2 - (-1)] = (-4 -3)*(-2 + 1) = -7*-1 = +7

More answers

[(-4) + (-3)]*[(-2 - (-1)] = (-4 -3)*(-2 + 1) = -7*-1 = +7

Q: How do you get the answer 7 using only numbers -4-3-2-1?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(5+7)*(5-3)=12*2=24

Yes you can do that

3+7-9=1 3 + 7 = 10 '10 - 9=1

8

1+2+3+4+5+6+7+8+9 = 45

Related questions

8 plus 1 , minus 5, plus 7 + 13

== == == == == == == == == ==

(5+7)*(5-3)=12*2=24

Yes you can do that

7 + 9 + 8*1

Yes just add them up.

Yes, you can do 12 + 7 + 5 = 24

7 x 5 - 9 - 2 = 24

(5 x 1) + 7 + 7 + 3 + 3 = 25

(18 + 16)/sqrt(4) + 7 = 34/2 + 7 = 17 + 7 = 24.

It's done by: (7+4+1) times 2 = 24

There are 9*9*8*7 = 4536 of them.